Marginalizacja osób z ograniczeniami sprawności na skutek zaburzeń psychicznych - Brzezińska, Anna Izabela; Zwolińska, Kamila (My University, 2010)
This paper presents the results of a study carried out with the use of the Social Research Questionnaire, a tool created for the needs of the scientific study project Ogólnopolskie badanie sytuacji potrzeb i mo'liwosci osób niepełnosprawnych (Nation-wide Study of the Situation, Needs and Prospects of People with Disabilities); for the purposes of our research, results of the second stage of that study, completed in 2009, were used. The results obtained confirm the hypothesis that individuals with mental disorders are a group most likely to be marginalized, as well as face social exclusion. The problem of marginalization involves numerous aspects of their lives: they feel more alienated than people with other types of disability, they undertake professional activity less often, finish education at a lower level as well as assessing their own satisfaction with life and general health as significantly worse. The phenomena of marginalization and social exclusion manifest themselves in this group at two levels. The first is linked to the fact of being a person with a disability, while the other level involves the fact that it was a mental disorder that was diagnosed as the fundamental source of disability, and is closely linked to self-marginalization.
Marginalization of people with disabilities connected with mental disorders
W artykule zaprezentowano wyniki badan przeprowadzonych Kwestionariuszem badan społecznych - KBS, który został stworzony na potrzeby projektu o charakterze naukowo-badawczym pt.: Ogólnopolskie badanie sytuacji potrzeb i możliwości osób niepełnosprawnych. Wykorzystano rezultaty drugiego etapu badan zrealizowanego w 2009 roku. Uzyskane wyniki potwierdzają hipotezę, i- osoby z zaburzeniami psychicznymi to grupa najbardziej nara-ona na marginalizacje, a tak-e wykluczenie społeczne. Problem marginalizacji przejawia się w wielu aspektach życia społecznego tych osób. Czuja się one bardziej wyobcowane niżeli reszta osób niepełnosprawnych, rzadziej podejmują aktywność społeczno-zawodowa, maja niższy poziom wykształcenia oraz istotnie ni-ej oceniają swoje zadowolenie z życia oraz stan zdrowia. Zjawisko marginalizacji i wykluczenia społecznego w badanej grupie manifestuje się na dwóch poziomach. Pierwszy poziom jest związany z faktem bycia osoba niepełnosprawna, drugi poziom dotyczy faktu zdiagnozowania zaburzeń psychicznych jako podstawowej przyczyny ograniczenia sprawności i wiąże się z automarginalizacją.
Keywords: aktywnosc społeczna; automarginalizacja; aktywnosc zawodowa; dyskryminacja; marginalizacja; ograniczenie sprawności; podwójne wykluczenie; stygmatyzacja; zaburzenia psychiczne; disability; discrimination; double exclusion; exclusion; inclusion; marginalization; mental disorders; professional activity; self-marginalization; social activity; stigmatization